2012
DOI: 10.1089/jpm.2011.0506
|View full text |Cite
|
Sign up to set email alerts
|

End of Life and Women Aging with a Disability

Abstract: Approximately 21 million noninstitutionalized Americans with physical disabilities will ultimately face end-oflife [EOL] issues. Studies have documented disparate care and poorer outcomes for persons with preexisting disabilities who have life-limiting illnesses, which raises the question of how EOL experiences may differ for these individuals. The aim of this qualitative, descriptive study was to explore how EOL issues might emerge within the life stories of women aging with functional disabilities. Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…10,11,18 Additional barriers to disability support workers provision of quality end-of-life care are fear of the unknown and not expecting to have to do this as part of their job. 8,15,19 This supports our study findings which identified similar challenges faced by disability support workers when their clients with long-standing physical disability transitioned to requiring end-of-life care.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…10,11,18 Additional barriers to disability support workers provision of quality end-of-life care are fear of the unknown and not expecting to have to do this as part of their job. 8,15,19 This supports our study findings which identified similar challenges faced by disability support workers when their clients with long-standing physical disability transitioned to requiring end-of-life care.…”
Section: Discussionsupporting
confidence: 85%
“…Discrimination within the healthcare system has led to unequal health outcomes for people with disability, including at end of life, with far reaching consequences. 15,24,25 Importantly, this study recognises that family, whether in a caring role or not, have been witness to and may have experienced this discrimination as a result of their support of the person with disability. 26 The complexity of the role of family was raised by participants in this study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations